Saskatchewan Joins British Columbia in Introducing an Immunize or Mask Policy - Amy Zarzeczny (McMaster University Library Press, 2015)
Seasonal influenza is a contagious respiratory infection for which certain populations, particularly seniors in long-term care and medically vulnerable individuals receiving care as in-patients in health care facilities, are at heightened risk for serious complications. Accordingly, annual influenza vaccination is a public health objective. In September 2014, Saskatchewan joined British Columbia and became the second Canadian province to implement a so-called "immunize or mask" policy that applies to individuals in patient care locations including, but not limited to, health care workers. The policy is focused on promoting patient safety by reducing the transmission of influenza in regional health authority facilities. On its face, this policy aligns well with the Ministry of Health's commitments to patient-centered care, to quality improvement, and to thinking and acting as one system. The policy will be adopted and implemented by each of the 13 regional health authorities and the single cancer agency in the province. Preliminary evaluation is anticipated after this first year of policy implementation. La grippe saisonnière est une infection respiratoire contagieuse qui peut engendrer de sérieuses  complications pour certaines populations, particulièrement les personnes âgées dépendantes et les individus médicalement vulnérables recevant des soins hospitaliers en établissement. C'est pour cette raison que la vaccination annuelle contre la grippe est un objectif de santé publique. Le Saskatchewan a rejoint la Colombie Britannique en septembre 2014 pour devenir la seconde province du Canada à mettre en place une politique dite "le vaccin ou le masque" s'appliquant aux personnes fréquentant les établissements de soins, entre autres les professionels de soins. Cette politique vise à promouvoir la santé des patients en réduisant la transmission de la grippe au sein des établissements de soins publics. À première vue, elle s'aligne bien avec les objectifs affichés par le Ministère de la Santé de soins centrés sur le patient, d'amélioration de la qualité des soins, et d'unité de pensée et d'action du système. La politique sera adoptée et mise en place par chacune des 13 autorités régionales de santé et l'unique agence pour le cancer de la province. Une première évaluation est attendue un an après la mise en place.